2023
DOI: 10.3390/jcto1020006
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Substance P (SP) on the Corneal Epithelium

Abstract: In 1931, Von Euler and Gaddum isolated substance P (SP), an undecapeptide from the tachykinin family, from equine brain and intestine tissue extracts. Numerous types of cells, including neurons, astrocytes, microglia, epithelial, and endothelial cells, as well as immune cells including T-cells, dendritic cells, and eosinophils, are responsible for its production. The corneal epithelium, immune cells, keratocytes, and neurons all express the two isoforms of NK1R, which has the highest affinity for SP. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 170 publications
0
1
0
Order By: Relevance
“…Another study by Miller et al found a dense network of SP immunoreactive axons in the cornea's substantia propria, subepithelial layer, and corneal epithelium [26]. Subsequently, it was discovered that SP has important functions in corneal re-epithelialization after injury [13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Miller et al found a dense network of SP immunoreactive axons in the cornea's substantia propria, subepithelial layer, and corneal epithelium [26]. Subsequently, it was discovered that SP has important functions in corneal re-epithelialization after injury [13,27,28].…”
Section: Discussionmentioning
confidence: 99%